2003
DOI: 10.1023/a:1026077825584
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This review deals with recent data on the structure and biochemical properties of dehydrins, proteins that are normally synthesized in maturating seeds during their desiccation, and also in vegetative tissues of plants treated with abscisic acid or exposed to environmental stress factors that result in cellular dehydration. The dehydrins are considered as stress proteins involved in formation of plant protective reactions against dehydration. The generally accepted classification of dehydrins is based on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(70 citation statements)
references
References 73 publications
1
61
0
Order By: Relevance
“…Dehydrins act as chaperons, stabilizing vesicles, proteins, and membrane structures in stressed plants (Close, 1997;Allagulova et al, 2010). However, the precise function of these proteins remains unknown.…”
Section: Differential Expression Of Sccbf1 Pyrroline-5-carboxylate Smentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydrins act as chaperons, stabilizing vesicles, proteins, and membrane structures in stressed plants (Close, 1997;Allagulova et al, 2010). However, the precise function of these proteins remains unknown.…”
Section: Differential Expression Of Sccbf1 Pyrroline-5-carboxylate Smentioning
confidence: 99%
“…Studies in wheat have reported an association between the CBF genes and LEA expression upon abiotic stress Kobayashi et al, 2005). Dehydrins like genes (DHNs) are members of the LEA protein family, and the most abundant class of dehydrins, such as the barley dehydrins DHN1, DHN2, DHN3, DHN4, DHN6, and DHN9, is induced in response to drought or ABA (Allagulova et al, 2010). Some studies in potato and tobacco have also demonstrated an association of CBF overexpression with LEA protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic rates are lowered which create energy imbalance. Freezing (0°C and below) temperatures cause membrane injury [3], decrease the respiration rate and ATP content [4], resulting in poor germination, reduced seedling emergence, decreased seedling vigour, and ultimately severe loss in yield of the food crops of tropical and subtropical origins [5][6][7][8][9]. Embryos, excised from seed coats of soybeans, leak profusely during the first minutes of imbibition.…”
Section: Germination Physiology In Low Temperaturementioning
confidence: 99%
“…Most of dehydrins are associated mainly with the process of embryogenesis, but they can also be accumulated in vegetative parts during the plant lifecycle. Generally, dehydrins are enriched with glycine and lysine residues, but they lack cysteine and tryptophan (Allagulova et al, 2003). The characteristic feature of all dehydrins is conservative sequences denominated as K-, S-and Y-segmets which are their structural attribute.…”
Section: Introductionmentioning
confidence: 99%